Optimizing adaptive responses through individualized interval hypoxic training - Babashev, Abdrazak; Malikovna, Zhylkyshybaeva M; Maralovich, Kalekeshov A; Mukhambetovna, Shaikhynbekova R; Bektemirova, Aigerim; Mukhatovna, Baibolatova L; Iliyasovna, Otarova N; Bedelovna, Barmenkulova B; Abdikarimova, Gaukhar (Caspian journal of environmental sciences, 2024)
Interval hypoxic training (IHT) has emerged as a key strategy in enhancing physiological adaptations in both human and animal subjects. This study introduces a groundbreaking application of IHT innovations, focusing on individualized training protocols, advanced monitoring technology, and multidisciplinary collaboration within the context of a case study conducted in Kazakhstan. Our research aimed to assess the practical impact of these innovations on adaptive responses and present empirical results from this unique application. In this case study, individualized training protocols were meticulously designed based on participants' genetic and fitness profiles. State-of-the-art wearable devices facilitated real-time monitoring of physiological parameters during IHT sessions. Multidisciplinary collaboration united experts from diverse fields, enriching our understanding of IHT's mechanisms and applications. The results from this case study revealed statistically significant improvements in physiological parameters. A comparative analysis against traditional training methods showcases the superiority of individualized IHT, with participants experiencing a 15% increase in cardiovascular fitness, a 10% improvement in respiratory functions, and a remarkable 20% enhancement in endurance (p < 0.001). These numerical outcomes underscore the practical significance of the introduced innovations in optimizing adaptive responses to intermittent hypoxia. Our findings suggest that the tailored application of IHT protocols, combined with advanced monitoring technology and multidisciplinary collaboration, yields substantial physiological benefits. This research not only advances our comprehension of IHT but also emphasizes its practical significance in optimizing adaptive responses in both human and animal physiology. The demonstrated improvements in cardiovascular fitness, respiratory functions, and endurance highlight the potential for these innovations to revolutionize precision training and healthcare regimens, especially in diverse geographic regions.